Кон Bonnie Mann, Women’s Liberation and the Sublime: Feminism, Postmodernism, Environment: Për Bonnie Mann, Women’s Liberation and the Sublime: Feminism, Postmodernism, Environment - Badarevski, Bobi; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Bobi Badarevski | Боби Бадаревски Title (Macedonian): Кон Bonnie Mann, Women’s Liberation and the Sublime: Feminism, Postmodernism, Environment Title (Albanian): Për Bonnie Mann, Women’s Liberation and the Sublime: Feminism, Postmodernism, Environment Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 209-214 Page Count: 6 Citation (Macedonian): Боби Бадаревски, „Кон Bonnie Mann, Women’s Liberation and the Sublime: Feminism, Postmodernism, Environment“, Идентитети: списание за политика, род и култура, т. 6, бр. 1 (зима 2007): 209-214. Citation (Albanian): Bobi Badarevski, „Për Bonnie Mann, Women’s Liberation and the Sublime: Feminism, Postmodernism, Environment“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 1 (Winter 2007): 209-214.